Robust Monetary Policy in a Currency Union - Kuznetsova, Olga (Panoeconomicus, 2012)
A great number of recent researches have found importance of country specific shocks for optimal monetary policy construction in the context of a currency union. This however has been almost completely overlooked by the analysis of optimal monetary policy under model uncertainty. The main purpose of our work is to fill this gap. By using a model of a two-country currency union with sticky prices, we have derived robust monetary policy that works reasonably well even in the worst case of model perturbations. We find some anti-attenuation effect of uncertainty, and show that the central bank’s optimal reaction to economic shocks becomes more aggressive with an increase in the extent of misspecification.Key words: Model uncertainty, Robust monetary policy, Currency union.JEL: E52, E58.